When Healthy Eating is Carried to the Extreme. Issue 3 (May 2017) - Morin, Karen
Abstract : Orthorexia nervosa is a fairly new nonspecific eating disorder, and given societal emphasis on health and healthy diets, nurses should be familiar with it and the consequences. Our nutrition expert, Dr. Morin, offers advice on how to identify those with orthorexia nervosa. This is the last column by Dr. Morin and we thank her for many years of service to MCN as the nutrition columnist.